The Pedagogy of Death and education in the wake of the pandemic: Implications for comprehensive teacher education encompassing awareness and the biographical dimension - de la Herrán Gascón, Agustín; Rodríguez Herrero, Pablo; Ahmed-Mohamed, Karim; García Sempere, Pablo José (Death Studies, 2025)
The pandemic has had a global impact on society and, consequently, also on schools. The aim of this study was to explore both teachers’ attitudes toward an education that includes death, and the impact of the pandemic on the treatment of death in the classroom. A survey using the DEAS-T instrument was administered to a total of 192 teachers from Spanish schools. Among the most salient results were: (1) participants had a moderately positive attitude toward the Pedagogy of Death, with influential variables such as gender, teachers’ academic profiles, and consequences of the pandemic; (2) the pandemic had made the subject of death somewhat more present in the classroom. Comprehensive teacher training in the Pedagogy of Death, encompassing awareness of the educational potential of death, didactic competences, and the biographical dimension of the teacher, is called for.
Keywords: Pedagogy of Death; pandemic; teachers; education; Spain